社交自我效能與害怕負面評價在害羞對憂鬱之影響的中介效果 Mediation Effects of Social Self-Efficacy and Fear of Negative Evaluation on the Influence of Shyness on Depression - 蘇素美 Su-Mei Su (National Taiwan Normal University, 2017)
本研究旨在探討社交自我效能和害怕負面評價在害羞對憂鬱之影響的中介效果。本研究以407 位大學生為對象，以「害羞量表修訂版」、「社交自我效能量表」、「害怕負面評價量表」及「台灣人憂鬱症量表」為研究工具，採用結構方程模式進行分析。研究的主要結果為：一、害羞對大學生的社交自我效能有負向的直接效果，對害怕負面評價有正向的直接效果。二、社交自我效能對大學生的憂鬱有負向的直接效果，而害怕負面評價對大學生的憂鬱有正向的直接效果。三、社交自我效能和害怕負面評價可以完全中介害羞和憂鬱之間的關係。針對研究結果，本研究對教育與輔導，以及未來的研究方向提出建議。 The purpose of this study was to explore the mediation effects of social self-efficacy and fear of negative evaluation on the influence of shyness on depression. The subjects were 407 undergraduates in Taiwan. Structural equation modeling was used to analyze the data. The following results were revealed: (1) Shyness has a direct negative effect on undergraduates' social self-efficacy and a direct positive effect on fear of negative evaluation. (2) Social self-efficacy has a direct negative effect on undergraduates' depression. Fear of negative evaluation has a positive direct effect on depression. (3) Social self-efficacy and fear of negative evaluation mediate the relationships between shyness and depression. Suggestions and implications for education, counseling, and future research are discussed.